Electrolytic aluminum anode high-conductivity high-temperature anti-oxidation life-extending coating and preparation method and application thereof
Patent Information
- Application Number
- CN202411501074.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-10-25
AI Technical Summary
同时,阳极钢爪在电解铝生产过程中,会受到热应力、电磁力和碰撞力的破坏,这些力量会导致钢爪变形、损坏,甚至出现裂纹或掉角,从而影响其使用寿命
(1)本发明提供的一种电解铝阳极高导电高温防氧化延寿的涂料,成分中添加一定比例碳化硅与石墨烯以增强涂层的力学性能和导电性能;添加以钠长石和滑石为主要成分的成釉剂,两者在高温下可以形成釉面,一定程度上填补了由于受热不均或涂层基本结构相热膨胀系数与阳极钢爪或炭块不一致而导致的裂纹,减少了阳极炭块与周围氧化性氛围的接触,从而降低了阳极的损耗;此外,成釉剂中还添加有少量的镧系氧化物,稀土元素的添加使氧化铝形成固溶体,促进氧化铝晶粒细化,提高附着性、热稳定性及断裂韧性,同时稀土元素的添加也对涂层起到一定的强化作用。
Smart Images

Figure CN119286288B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new metallurgical materials technology, specifically relating to a high-conductivity, high-temperature anti-oxidation and life-extending coating for electrolytic aluminum anodes and its preparation method, as well as the application of the above-mentioned high-conductivity, high-temperature anti-oxidation and life-extending coating for electrolytic aluminum anodes. Background Technology
[0002] Anode carbon blocks refer to carbon blocks produced using petroleum coke and pitch coke as aggregates and coal tar pitch as a binder, used as anode materials in prebaked aluminum electrolytic cells. During aluminum electrolysis, the anode must withstand the high temperatures from molten alumina for extended periods, as well as the oxidizing environment created by carbon dioxide, hydrogen fluoride, cryolite, oxygen, and atomic oxygen generated at high temperatures. This leads to continuous loss of anode carbon blocks within a single working cycle, resulting in problems such as slag shedding, hot cells, cathode damage, increased energy consumption, lower yield, and product impurity. Existing methods to address this issue include improving the purity of the anode carbon blocks and spraying a protective layer onto the anode surface. Among these methods, spraying a protective layer offers advantages such as low cost and good results.
[0003] Electrolytic anode claws, also known as electrolytic claws, are core components of aluminum electrolysis equipment, primarily used to connect the anode and transmit current. During casting, to save costs, low-carbon cast steel is typically used as the main material, with some recycled steel claws added. This material selection aims to ensure good conductivity while reducing costs. However, during aluminum electrolysis, the anode claws come into contact with electrolytes, electrode feed, air, and electrolytic flue gas. These substances contain moisture and other chemical components, which react chemically with the steel claws under high temperatures, forming oxides and causing corrosion. Especially when the temperature inside the electrolytic cell reaches above 100°C, adsorbed moisture evaporates into water vapor, escaping upwards from pores and crevices, causing further corrosion. Simultaneously, during aluminum electrolysis, the anode claws are subjected to thermal stress, electromagnetic forces, and impact forces. These forces can cause deformation, damage, and even cracks or chipping, thus affecting their service life. Furthermore, the raw materials used in the production of anode steel claws are often scrap steel, mixed steel, and end-of-life steel claws, resulting in large fluctuations in alloy element content. In particular, excessively high levels of impurity elements such as C, S, and P increase the resistivity of the steel claws. In addition, improper casting processes during production can easily lead to defects such as shrinkage cavities, porosity, and inclusions inside the steel claws, reducing the effective conductive area and further increasing resistance. These factors combined result in increased resistivity of the anode steel claws, affecting their conductivity and service life.
[0004] In some existing solutions, nano-high-temperature anti-oxidation coatings specifically designed for electrolytic aluminum anodes are used to protect the anode carbon blocks. However, these nano-high-temperature anti-oxidation coatings often involve cumbersome preparation processes and complex raw material ratios, and their conductivity is often poor, leading to increased energy consumption and ultimately underutilization of production capacity. Furthermore, the coating is prone to cracking under high-temperature oxidation conditions and lacks self-healing capabilities, causing the anode carbon blocks and steel claws to be exposed to the high-temperature oxidation environment again. Other solutions attempt to fill coating cracks by adding special components, but these components are prone to reacting with the molten aluminum, leading to aluminum contamination or reduced production.
[0005] Based on this, an electrolytic aluminum anode coating is provided, which protects the anode carbon block and anode steel claw from oxidation and reduces losses as much as possible, while simplifying the preparation process, reducing the preparation cost, and improving the conductivity to reduce production energy consumption. This is of great significance for the development of low energy consumption and high output in the electrolytic aluminum industry and is also a technical problem that urgently needs to be solved. Summary of the Invention
[0006] One of the objectives of this invention is to provide a coating for electrolytic aluminum anodes that is highly conductive, high-temperature resistant to oxidation, and extends their service life, thereby protecting the anode carbon block and anode steel claw from loss due to high-temperature oxidation and improving conductivity to reduce production energy consumption.
[0007] The second objective of this invention is to provide a method for preparing a coating for electrolytic aluminum anodes that has high conductivity, high temperature resistance, oxidation prevention, and extended service life.
[0008] The third objective of this invention is to provide a coating for high conductivity, high temperature resistance, oxidation prevention, and life extension of electrolytic aluminum anodes, which is applied in the electrolytic aluminum industry.
[0009] One of the technical solutions adopted by this invention to achieve its objective is: to provide a coating for electrolytic aluminum anodes that has high conductivity, high temperature resistance, oxidation prevention, and extended service life, which is composed of the following raw materials by weight: Refined bauxite 34-50 parts; water 20-25 parts; silicon carbide 20-30 parts; graphene 1.5-3 parts; glaze agent 4-6 parts; film-forming agent 2.1-2.2 parts; modifier 0.3-0.4 parts; The glazing agent is composed of albite, talc and lanthanide oxides; the content of lanthanide oxides in the glazing agent is 0.3 wt.%-0.7 wt.%.
[0010] The overall concept of this invention is as follows: The high-conductivity, high-temperature, anti-oxidation, and life-extending coating for electrolytic aluminum anodes provided by this invention uses refined bauxite as the basic component and silicon carbide as the main reinforcing component. Silicon carbide can not only refine the grains of alumina to achieve the purpose of fine grain strengthening, but also, as a substance with a Mohs hardness second only to diamond, silicon carbide has excellent mechanical properties, which can enhance the mechanical properties of the coating to a certain extent. In addition, as a semiconductor material, silicon carbide has a certain promoting effect on the passage of anolyte current, which is beneficial to reducing energy consumption.
[0011] Graphene is used as an auxiliary reinforcing component. Because the carbon atoms in graphene are sp2 hybridized, with one unhybridized electron in one of the 2p orbitals, a large π bond similar to that in benzene is formed. These π electrons can move freely, and the Dirac cone structure, where the energy states of electrons and holes are very close, allows electrons in graphene to move at extremely high speeds. Therefore, it has excellent electrical conductivity, effectively improving the conductivity of the coating and reducing energy consumption. Furthermore, due to the excellent mechanical properties of graphene, the adhesion, thermal stability, and fracture toughness of the coating are improved. In addition, graphene itself possesses certain lubricating properties; doping with graphene helps improve the friction resistance of the coating surface and reduces electrolyte adhesion to the coating and anode.
[0012] A mixture of albite and talc is used as the main component of the glazing agent. At high temperatures, the two components form a glaze, which to some extent fills cracks caused by uneven heating or inconsistencies in the thermal expansion coefficients of the coating's basic structural phases with the anode steel claws or carbon blocks. This reduces the contact between the anode carbon block and the surrounding oxidizing atmosphere, thereby lowering anode loss. A small amount of lanthanide oxides is also added to the glazing agent. The addition of rare earth elements causes the alumina in the ceramic matrix continuous phase to form a solid solution, promoting alumina grain refinement and improving adhesion, thermal stability, and fracture toughness. Simultaneously, the addition of rare earth elements also strengthens the coating to a certain extent.
[0013] Furthermore, the refined bauxite contains 97wt.%-99wt.% alumina. Compared to alumina, refined bauxite inevitably incorporates certain impurity elements (such as iron, gallium, calcium, magnesium, silicon, etc.) during the alumina extraction process. These elements are similar to the constituent elements of albite and talc, and can complement each other to improve the fracture filling effect.
[0014] Furthermore, the composition of the glazing agent, by weight percentage, is 32.5%-47.5% talc, 52.5%-67.5% albite powder, and 0.3%-0.7% lanthanide oxides. In the glazing agent used in this invention, talc and albite can form a glaze at high temperatures to fill cracks on the surface of the steel claw coating, and the glaze-forming substances do not react with the molten aluminum, thus avoiding contamination of the molten aluminum.
[0015] Furthermore, the lanthanide oxides are in powder form and can be commercially available products or produced from xenotime ore. The lanthanide oxides include one or more combinations of lanthanum oxide, cerium oxide, neodymium oxide, and europium oxide.
[0016] Preferably, the method for preparing lanthanide oxides includes: acid leaching of xenotime ore to obtain a solution containing lanthanide ions; adding an alkaline solution to the solution to obtain a precipitate; and heat-treating the precipitate to obtain lanthanide oxides. The lanthanide oxides used in this invention are obtained from xenotime ore through acid leaching, alkaline precipitation, and calcination decomposition. This method not only effectively separates lanthanide elements but also has the advantage of low cost.
[0017] Further, the modifier is selected from silane coupling agents or sodium dodecylbenzenesulfonate. Preferably, the modifier is 3-(methacryloyloxy)propyltrimethoxysilane (silane coupling agent KH-570).
[0018] Further, the film-forming agent is selected from polyurethane, polyacrylate, and polyvinylpyrrolidone. Preferably, the film-forming agent is selected from polyvinylpyrrolidone, which contains a nitrogen-containing heterocyclic ring and a ketone carbonyl group containing an oxygen atom in its structure. It has a strong effect on silane coupling agents and other inorganic components, and can effectively form a film on the anode steel claw and / or anode carbon block with strong adhesion.
[0019] The second technical solution adopted by the present invention to achieve the objective is: to provide a method for preparing a coating according to one of the objectives of the present invention, comprising the following steps: S1. The refined bauxite is ball-milled, and the ball-milled product is mixed with a modifier and then coated and modified to obtain the first product. S2. The first product is mixed with silicon carbide and graphene, and then ball-milled to obtain the second product. S3. Mix the film-forming agent with water to obtain a film-forming agent solution; mix sodium feldspar and talc, and then crush and ball-mill them to obtain the third product; S4. The second and third products are mixed with lanthanide oxide powder and added to the film-forming agent solution to obtain the fourth product; S5. Place the fourth product in a closed and pressurized environment, heat and mix for a certain time to obtain a coating for high conductivity, high temperature, anti-oxidation and life extension of electrolytic aluminum anode.
[0020] Further, in step S1, the ball-to-material ratio for ball milling is 5:1, and zirconia milling balls with diameters of 5 mm, 7 mm and 12 mm are mixed in a ratio of (15-20):(4-6):(2-3) as the milling medium. The milling time is 2.5-4.5 h, and the particle size of the first product is 450-600 mesh.
[0021] Furthermore, in step S1, a powder modification machine is used for coating modification, and the modification time is 1-2 hours.
[0022] Further, in step S2, the ball-to-material ratio for ball milling is 8:1, and zirconia milling balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm are mixed in a ratio of (40-55):(15-23):(3-7) as the milling medium. The milling time is 4-6 hours, and the particle size of the second product is 650-750 mesh.
[0023] Further, in step S3, a roller crusher is first used to continuously crush the product for 1-2 hours at a power of 25-35kW. Then, the crushed product is ball-milled. The ball-to-material ratio for ball milling is 3:1. Stainless steel grinding balls with diameters of 6mm, 8mm and 10mm are mixed in a ratio of (10-12):(4-6):(0.6-1) as the ball milling medium. The ball milling time is 0.5-1.5 hours. The particle size of the third product is 750-950 mesh.
[0024] Furthermore, in step S5, the pressure is 1.2-1.5 MPa, the heating temperature is 130-170℃, the mixing stirring speed is 50-70 r / min, and the heating time is 2.5-3.5 h.
[0025] The third objective of this invention is achieved by providing an application of a coating for high conductivity, high temperature, anti-oxidation, and life-extending properties of electrolytic aluminum anodes. The coating is the coating described in the first objective of this invention, or the coating prepared by the preparation method described in the second objective of this invention.
[0026] Furthermore, the application includes: applying the coating to the surface of the anode carbon block and / or anode steel claw by spraying.
[0027] Furthermore, the coating thickness on the surface of the anode carbon block is 0.7-1.1 mm, and the coating thickness on the surface of the anode steel claw is 0.5-0.9 mm.
[0028] Preferably, the coating is applied to the surface of the anode carbon block and the anode steel claw by spraying. The anode carbon block is made from anthracite and metallurgical coke as the main raw materials, and coal tar pitch is used as a modifier; the anode steel claw is made from low-carbon steel and scrap steel claws by casting.
[0029] The high-conductivity, high-temperature anti-oxidation, and life-extending coating for electrolytic aluminum anodes provided by this invention can be applied to the surface of both the anode carbon block and the anode steel claw, thereby protecting the anode carbon block and the anode steel claw and preventing them from being lost due to high-temperature oxidation during the electrolytic aluminum process. It can also improve conductivity to reduce production energy consumption.
[0030] Furthermore, the coating provided by this invention, applied to the surface of an anode steel claw cast from low-carbon steel and scrap steel claws, can compensate for the poor oxidation resistance and high-temperature resistance of low-cost steel claws. On the one hand, the coating can isolate moisture and other chemical substances in the high-temperature oxidizing environment, preventing corrosion of the anode steel claw. On the other hand, the self-healing coating can improve the high-temperature resistance of the anode steel claw, preventing deformation, damage, or cracking under thermal stress, electromagnetic force, and impact force. In addition, the addition of graphene in the coating improves conductivity, compensating for the increased resistivity and poor conductivity caused by impurities in the scrap steel claw raw materials. The coating improves the overall performance and application performance of the anode steel claw, extends its service life, reduces energy consumption in electrolytic aluminum production, and ensures the purity of the molten aluminum.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention provides a coating for electrolytic aluminum anode with high conductivity, high temperature, anti-oxidation and extended service life. A certain proportion of silicon carbide and graphene are added to the composition to enhance the mechanical and electrical properties of the coating. A glazing agent with sodium feldspar and talc as the main components is added. The two can form a glaze at high temperature, which to a certain extent fills the cracks caused by uneven heating or the inconsistency between the thermal expansion coefficient of the basic structural phase of the coating and the anode steel claw or carbon block, and reduces the contact between the anode carbon block and the surrounding oxidizing atmosphere, thereby reducing the anode loss. In addition, a small amount of lanthanide oxides are added to the glazing agent. The addition of rare earth elements makes alumina form a solid solution, promotes the refinement of alumina grains, and improves adhesion, thermal stability and fracture toughness. At the same time, the addition of rare earth elements also plays a certain strengthening role in the coating.
[0032] (2) The coating provided by the present invention is a high-conductivity, high-temperature anti-oxidation and life-extending coating for electrolytic aluminum anodes. It can protect the anode carbon block and anode steel claw from oxidation as much as possible and reduce losses, while simplifying the preparation process and reducing the preparation cost. At the same time, due to the doping of graphene, the conductivity is improved, so it can reduce the production energy consumption and cost of electrolytic aluminum to a certain extent, and has the prospect of promotion and application. Attached Figure Description
[0033] Figure 1 A schematic flowchart illustrating the preparation method of a high-conductivity, high-temperature, anti-oxidation, and life-extending coating for electrolytic aluminum anodes provided by this invention; Figure 2 A photograph of a sample of an anode steel claw and carbon block coated with the coating prepared in Example 1 of this invention; Figure 3 A photograph of a carbon block coated with the paint prepared in Example 1 of this invention, which is currently undergoing testing. Detailed Implementation
[0034] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.
[0036] This invention provides a coating for electrolytic aluminum anodes that provides high conductivity, high temperature resistance, oxidation prevention, and extended service life. By weight, it comprises the following raw materials: 34-50 parts refined bauxite; 20-25 parts water; 20-30 parts silicon carbide; 1.5-3 parts graphene; 4-6 parts glazing agent; 2.1-2.2 parts film-forming agent; and 0.3-0.4 parts modifier. The refined bauxite contains 97 wt.%-99 wt.% alumina; the glazing agent, by weight percentage, consists of 32.5%-47.5% talc, 52.5%-67.5% albite, and 0.3%-0.7% lanthanide oxides; the film-forming agent is selected from polyurethane, polyacrylate, and polyvinylpyrrolidone; and the modifier is selected from silane coupling agent or sodium dodecylbenzenesulfonate.
[0037] The present invention will be further described below with reference to specific embodiments, but these are not intended to limit the scope of the invention.
[0038] The raw materials and their weight percentages involved in the various embodiments and comparative examples of the present invention are shown in Table 1 below.
[0039] Table 1
[0040] In the table above, the film-forming agent is polyvinylpyrrolidone, and the modifier is 3-(methacryloyloxy)propyltrimethoxysilane (silane coupling agent KH-570); the lanthanide oxides are selected from one or more combinations of lanthanum oxide, cerium oxide, neodymium oxide, and europium oxide, and the purity of each is not less than 99.9%.
[0041] Example 1 This embodiment provides a coating for electrolytic aluminum anodes that has high conductivity, high temperature, anti-oxidation, and extended service life. By weight, it is composed of the following raw materials: 46 parts refined bauxite; 25 parts water; 20 parts silicon carbide; 2 parts graphene; 4.4 parts glazing agent; 2.2 parts film-forming agent; and 0.4 parts modifier.
[0042] The preparation method of the coating includes the following steps: Step 1: The refined bauxite was ball-milled with a ball-to-material ratio of 5:1. Zirconia grinding balls with diameters of 5mm, 7mm, and 12mm were mixed in a ratio of 18:5:2 as the grinding media. The ball milling time was 4 hours to obtain the ball-milled product. The ball-milled product was then mixed with a modifier and coated using a powder modifier for 1.5 hours to obtain the first product with a particle size of 450-600 mesh. Step 2: Mix the first product with silicon carbide and graphene, and then ball mill it. Set the ball-to-material ratio to 8:1. Use zirconia grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm in a quantity ratio of 45:20:5 as the ball milling medium. The ball milling time is 5 hours to obtain the second product with a particle size of 650-750 mesh. Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and continuously crush them for 2 hours using a 2PG-610X400 roller crusher at a power of 30kW. Then, ball mill the crushed product, setting the ball-to-material ratio to 3:1. Use stainless steel grinding balls with diameters of 6mm, 8mm, and 10mm mixed in a ratio of 11:5:0.8 as the ball milling medium. The ball milling time is 1 hour, resulting in a third product with a particle size of 750-950 mesh. Step 4: Mix the second and third products with lanthanide oxide powder and add them to the film-forming agent solution to obtain the fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.4 MPa, set the heating temperature to 150℃, the stirring speed during the heating process to 60 r / min, and the heating time to 3h, thus obtaining the high conductivity, high temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes.
[0043] Example 2 This embodiment provides a coating for electrolytic aluminum anodes that is highly conductive, high-temperature resistant, oxidation-resistant, and extends service life. By weight, it is composed of the following raw materials: 40 parts refined bauxite; 25 parts water; 20 parts silicon carbide; 3 parts graphene; 4.6 parts glazing agent; 2.1 parts film-forming agent; and 0.3 parts modifier.
[0044] The preparation method of the coating includes the following steps: Step 1: The refined bauxite is ball-milled with a ball-to-material ratio of 5:1. Zirconia grinding balls with diameters of 5mm, 7mm, and 12mm are mixed in a ratio of 15:4:2 as the grinding media. The ball milling time is 2.5 hours to obtain the ball-milled product. The ball-milled product is then mixed with a modifier and coated using a powder modifier for 1 hour to obtain the first product with a particle size of 450-600 mesh. Step 2: Mix the first product with silicon carbide and graphene, and then ball mill it. Set the ball-to-material ratio to 8:1. Use zirconia grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm in a quantity ratio of 40:15:3 as the ball milling medium. The ball milling time is 4 hours to obtain the second product with a particle size of 650-750 mesh. Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and continuously crush them for 1 hour using a 2PG-610X400 roller crusher at a power of 25kW. Then, ball mill the crushed product, setting the ball-to-material ratio to 3:1. Use stainless steel grinding balls with diameters of 6mm, 8mm, and 10mm mixed in a ratio of 10:4:0.6 as the ball milling medium. The ball milling time is 0.5 hours, resulting in a third product with a particle size of 750-950 mesh. Step 4: Mix the second and third products with lanthanide oxide powder and add them to the film-forming agent solution to obtain the fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.2 MPa, set the heating temperature to 130℃, the stirring speed during the heating process to 50 r / min, and the heating time to 2.5 h, thus obtaining a coating for high conductivity, high temperature, anti-oxidation and life extension of electrolytic aluminum anode.
[0045] Example 3 This embodiment provides a coating for electrolytic aluminum anodes that has high conductivity, high temperature, anti-oxidation, and extended service life. By weight, it is composed of the following raw materials: 50 parts refined bauxite; 20 parts water; 20 parts silicon carbide; 1.5 parts graphene; 6 parts glazing agent; 2.1 parts film-forming agent; and 0.4 parts modifier.
[0046] The preparation method of the coating includes the following steps: Step 1: The refined bauxite was ball-milled with a ball-to-material ratio of 5:1. Zirconia grinding balls with diameters of 5mm, 7mm, and 12mm were mixed in a ratio of 20:6:3 as the grinding media. The ball milling time was 4.5 hours to obtain the ball-milled product. The ball-milled product was then mixed with a modifier and coated using a powder modifier for 2 hours to obtain the first product with a particle size of 450-600 mesh. Step 2: Mix the first product with silicon carbide and graphene, and then ball mill it. Set the ball-to-material ratio to 8:1. Use zirconia grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm in a quantity ratio of 55:23:7 as the ball milling medium. The ball milling time is 6 hours to obtain the second product with a particle size of 650-750 mesh. Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and continuously crush them for 2 hours using a 2PG-610X400 roller crusher at a power of 35kW. Then, ball mill the crushed product, setting the ball-to-material ratio to 3:1. Use stainless steel grinding balls with diameters of 6mm, 8mm, and 10mm mixed in a ratio of 12:6:1 as the ball milling medium. The ball milling time is 1.5 hours, yielding a third product with a particle size of 750-950 mesh. Step 4: Mix the second and third products with lanthanide oxide powder and add them to the film-forming agent solution to obtain the fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.5 MPa, set the heating temperature to 170℃, the stirring speed during the heating process to 70 r / min, and the heating time to 3.5 h, thus obtaining a coating for high conductivity, high temperature, anti-oxidation and life extension of electrolytic aluminum anode.
[0047] Example 4 This embodiment provides a coating for electrolytic aluminum anodes that has high conductivity, high temperature, anti-oxidation, and extended service life. By weight, it is composed of the following raw materials: 34 parts refined bauxite; 25 parts water; 30 parts silicon carbide; 2.5 parts graphene; 6 parts glazing agent; 2.1 parts film-forming agent; and 0.4 parts modifier.
[0048] The preparation method of the coating includes the following steps: Step 1: The refined bauxite was ball-milled with a ball-to-material ratio of 5:1. Zirconia grinding balls with diameters of 5mm, 7mm, and 12mm were mixed in a ratio of 18:5:2 as the grinding media. The ball milling time was 4 hours to obtain the ball-milled product. The ball-milled product was then mixed with a modifier and coated using a powder modifier for 1.5 hours to obtain the first product with a particle size of 450-600 mesh. Step 2: Mix the first product with silicon carbide and graphene, and then ball mill it. Set the ball-to-material ratio to 8:1. Use zirconia grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm in a quantity ratio of 45:20:5 as the ball milling medium. The ball milling time is 5 hours to obtain the second product with a particle size of 650-750 mesh. Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and continuously crush them for 2 hours using a 2PG-610X400 roller crusher at a power of 25-35kW. Then, ball mill the crushed product, setting the ball-to-material ratio to 3:1. Use stainless steel grinding balls with diameters of 6mm, 8mm, and 10mm mixed in a ratio of 11:5:0.8 as the ball milling medium. The ball milling time is 1 hour to obtain a third product with a particle size of 750-950 mesh. Step 4: Mix the second and third products with lanthanide oxide powder and add them to the film-forming agent solution to obtain the fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.4 MPa, set the heating temperature to 150℃, the stirring speed during the heating process to 60 r / min, and the heating time to 3h, thus obtaining the high conductivity, high temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes.
[0049] Comparative Example This comparative example provides an electrolytic aluminum anode coating, which, by weight, is composed of the following raw materials: 57 parts refined bauxite, 31.5 parts water, 6 parts glazing agent (4.02 parts sodium feldspar, 1.95 parts talc, 0.03 parts lanthanide oxide), 5.1 parts film-forming agent, and 0.4 parts modifier.
[0050] The preparation method of the coating includes the following steps: Step 1: The refined bauxite was ball-milled with a ball-to-material ratio of 5:1. Zirconia grinding balls with diameters of 5mm, 7mm, and 12mm were mixed in a ratio of 18:5:2 as the grinding media. The ball milling time was 4 hours to obtain the ball-milled product. The ball-milled product was then mixed with a modifier and coated using a powder modifier for 1.5 hours to obtain the first product with a particle size of 450-600 mesh. Step 2: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and continuously crush them for 2 hours using a 2PG-610X400 roller crusher at a power of 30kW. Then, ball mill the crushed product, setting the ball-to-material ratio to 3:1. Use stainless steel grinding balls with diameters of 6mm, 8mm, and 10mm mixed in a ratio of 11:5:0.8 as the ball milling medium. The ball milling time is 1 hour to obtain a second product with a particle size of 750-950 mesh. Step 3: Mix the first product, the second product, and lanthanide oxide powder and add them to the film-forming agent solution to obtain the third product; Step 4: Place the third product in a closed environment with a pressure of 1.4 MPa, set the heating temperature to 150℃, the stirring speed during the heating process to 60 r / min, and the heating time to 3h to obtain the electrolytic aluminum anode coating.
[0051] Application performance testing The coating prepared in Example 1 of this invention was applied by spraying to the surfaces of the anode carbon block and the anode steel claw, respectively. The coating thickness on the anode carbon block was 0.9 mm, and the coating thickness on the anode steel claw was 0.7 mm. Application performance tests were conducted on the coated anode carbon block and anode steel claw, including high-temperature burning test, cryolite oxidation test, conductivity test, adhesion performance, aluminum melt contamination level, and service life. Specific test methods and results are as follows: Experiments were conducted in a 350KA electrolytic cell at an aluminum and electricity company in Ningxia. Tests showed that the coating prepared according to this invention adhered well to the carbon blocks and anode steel claws, with a smooth surface and no obvious holes or cracks. Figure 2 As shown. The service life of uncoated carbon blocks is 27-28 days, while the service life of carbon blocks coated with the coating of this invention is 30-31 days, and they maintain good working condition after coating, as shown in the attached figure. Figure 3 As shown below. The specific experimental procedure and data are as follows: Three carbon blocks coated with the coating prepared in Example 1 of this invention were numbered A1, A2, and A3, respectively, and three carbon blocks without coating were numbered AA1, AA2, and AA3, respectively. All three were placed in a muffle furnace, and the temperature was controlled at approximately 970°C. After calcination for 10 hours, the weight loss of the carbon blocks was measured. It was found that the uncoated carbon blocks experienced greater weight loss, while the coated carbon blocks experienced less weight loss. The specific weight loss rates are shown in Table 2 below. Table 2
[0052] Three carbon blocks coated with the coating prepared according to this invention were numbered B1, B2, and B3, respectively, and three carbon blocks without coating were numbered BB1, BB2, and BB3, respectively. All three groups of carbon blocks were placed in a muffle furnace, and each group was buried in 1000.0g of cryolite. The furnace was then calcined at 970℃. After 8 hours, the corrosion of the carbon blocks on the cryolite surface was observed. It was found that the carbon blocks coated with the coating showed less corrosion on the upper surface, with only the coating layer partially corroded, and the carbon block substrate showed slight corrosion. In contrast, the carbon blocks without coating showed more severe corrosion on the upper surface. The specific corrosion weight loss rates are shown in Table 3 below. Table 3
[0053] Three carbon blocks coated with the coating described in this invention were numbered C1, C2, and C3, respectively. Three carbon blocks coated with the coating prepared in the comparative example were numbered CC1, CC2, and CC3, respectively. Carbon blocks without any coating were numbered CCC1, CCC2, and CCC3. The two ends of these carbon blocks were connected to two electrodes, and then the carbon blocks were connected to a 350kA constant current source. The voltage across the carbon blocks was measured each time. The average voltage of the three groups coated with the coating prepared in this invention, the three groups coated with the coating of the comparative example, and the three groups without coating was compared. It was found that the voltage of the group coated with the coating prepared in this invention was lower than that of the other two groups. Due to the enhanced conductivity, the voltage across the two sides will decrease when the current is constant. The specific voltage values are shown in Table 4 below. Table 4
[0054] Six carbon blocks coated with the paint prepared in Example 1 of this invention were numbered D1, D2, D3, D4, D5, and D6, respectively. Adhesion was tested according to the national standard GB / T 5210. All test results reached level 0. The test results are shown in Table 5 below. Table 5
[0055] Three carbon blocks coated with the coating prepared in Example 1 of this invention were numbered E1, E2, and E3, respectively, and carbon blocks not coated with the coating of this invention were numbered EE1, EE2, and EE3. These were installed onto anode steel claws (coated with the coating prepared in Example 1 of this invention, with a coating thickness of 0.7 mm) prepared by casting from low-carbon steel and scrap steel claws. Since this was a destructive test, a service life test was conducted simultaneously to characterize the degree of aluminum melt contamination. The degree of aluminum melt contamination was characterized on day 7. It was found that the aluminum in the electrolytic cell coated with the coating of this invention had higher quality and fewer impurities, and the anode steel claws were only exposed on days 30-31. In contrast, the carbon blocks not coated with the coating exposed the anode steel claws on days 27-28. The sample working time and test results are shown in Tables 6 and 7 below. Table 6
[0056] Table 7
[0057] In conclusion, The high-conductivity, high-temperature, anti-oxidation, and life-extending coating for electrolytic aluminum anodes provided by this invention has strong adhesion. When applied to the surface of the anode carbon block and anode steel claw, it can significantly reduce the thermal weight loss of the anode carbon block and anode steel claw, and improve their corrosion resistance and conductivity. When applied to the electrolytic aluminum production process, this high-conductivity, high-temperature, anti-oxidation, and life-extending coating for electrolytic aluminum anodes can reduce the impurity content in the aluminum melt, ensure the quality of the aluminum melt, protect the anode carbon block and anode steel claw from oxidation as much as possible and reduce losses, while extending their service life, reducing production energy consumption and costs, and has promising prospects for promotion and application.
[0058] The above are merely preferred embodiments of the present invention and are not intended to limit the implementation methods and scope of protection of the present invention. Those skilled in the art should recognize that any equivalent substitutions and obvious changes made based on the content of this specification should be included within the scope of protection of the present invention.
Claims
1. A coating for high conductivity, high temperature resistance, oxidation prevention, and life extension of electrolytic aluminum anodes, characterized in that, By weight, it consists of the following raw materials: The composition includes: 34-50 parts refined bauxite; 20-25 parts water; 20-30 parts silicon carbide; 1.5-3 parts graphene; 4-6 parts glazing agent; 2.1-2.2 parts film-forming agent; and 0.3-0.4 parts modifier. The refined bauxite contains 97 wt.%-99 wt.% alumina. The modifier is a silane coupling agent. The glazing agent is composed of albite, talc and lanthanide oxides, with talc accounting for 32.5%-47.5% by weight, albite accounting for 52.5%-67.5% by weight, and lanthanide oxides accounting for 0.3%-0.7% by weight.
2. The coating according to claim 1, characterized in that, The film-forming agent is selected from one of polyurethane, polyacrylate, and polyvinylpyrrolidone.
3. A method for preparing a coating according to claim 1 or 2, characterized in that, Includes the following steps: S1. The refined bauxite is ball-milled, and the ball-milled product is mixed with a modifier and then coated and modified to obtain the first product. S2. The first product is mixed with silicon carbide and graphene, and then ball-milled to obtain the second product. S3. Mix the film-forming agent with water to obtain a film-forming agent solution; mix sodium feldspar and talc, and then crush and ball-mill them to obtain the third product; S4. The second and third products are mixed with lanthanide oxide powder and added to the film-forming agent solution to obtain the fourth product; S5. Place the fourth product in a closed and pressurized environment, heat and mix for a certain time to obtain a coating for high conductivity, high temperature, anti-oxidation and life extension of electrolytic aluminum anode.
4. The preparation method according to claim 3, characterized in that, The particle size of the first product is 450-600 mesh, the particle size of the second product is 650-750 mesh, and the particle size of the third product is 750-950 mesh.
5. The preparation method according to claim 3, characterized in that, In step S5, the pressure is 1.2-1.5 MPa, the heating temperature is 130-170℃, the mixing stirring speed is 50-70 r / min, and the heating time is 2.5-3.5 h.
6. The application of a coating for high conductivity, high temperature resistance, oxidation prevention, and life extension of electrolytic aluminum anodes, wherein the coating is the coating according to claim 1 or 2, or the coating prepared by the method according to any one of claims 3-5, characterized in that, The coating is applied to the surface of the anode carbon block and / or anode steel claw by spraying.
7. The application according to claim 6, characterized in that, The coating is applied to the surface of the anode carbon block and the anode steel claw by spraying; the anode carbon block is made from anthracite and metallurgical coke as the main raw materials and coal tar pitch as a modifier; the anode steel claw is made from low carbon steel and scrap steel claw by casting.
Citation Information
Patent Citations
Novel energy-saving corrosion-resistant anode steel claw for electrolyzing aluminum and design method thereof
CN109898101A
Prebaked anode anti-oxidation coating for electrolytic aluminum and preparation method of prebaked anode anti-oxidation coating
CN115895302A
Coating for aluminum electrolysis carbon anode, preparation method of coating and aluminum electrolysis carbon anode
CN118388986A